Utilization of Free Energy for Power Supply Using Magnetic Generators in Military Operations in Remote Areas - Rian Putra Eka Setiawan; Reza Setiawan (International Research & Development for Human Beings (IRDH), 2025)
This research aims to assist the primary duties of the Indonesian Army (TNI-AD) by utilizing a magnet generator with a free energy concept as a solution for energy supply in military operations, especially in remote areas where conventional energy sources are scarce and difficult to access. The magnet generator is designed to operate at low speeds, enabling it to charge military devices efficiently. By designing, testing, and analyzing the magnet generator optimized for low-speed operation, the research aims to ensure that the generator produces energy that can be used in remote military operation fields. The test results indicate that the generator is capable of producing high energy with an efficiency reaching 82.3% at 200 RPM. The energy produced is sufficient to charge military devices and provide a stable backup power supply. With this capability, the designed magnet generator can serve as a reliable power source to support military operations in hard-to-reach areas.